Operative Hysteroscopy: Experience in a Teaching Hospital - Cengiz, Hüseyin; Ekin, Murat; Kaya, Cihan; Keven, Can; Özel, Gül; Kaban, İşık; Yaşar, Levent (Fırat University, 2013)
Objective: The objective of this study was to determine the indications, success, and complications of operative hysteroscopy performed at a teaching hospital Materials and Methods: A two-year retrospective cohort study was done of women undergoing operative hysteroscopy at Bakırkoy Dr Sadi Konuk Teaching and Research Hospital from January 2010 to January 2012. Results: 120 patients were included in the study. The mean age of patients undergoing operative hysteroscopy was 44.33 years. The most common indication for operative hysteroscopy was endometrial polyp. There were four procedure-related complications. Conclusion: Hysteroscopy is a safe and effective minimally invasive procedure with a low rate of complications.

Amaç: Bu çalışmanın amacı, bir eğitim hastanesinde gerçekleştirilen operatif histeroskopilerin endikasyonları, başarı ve komplikasyonlarını tespit etmektir. Gereç ve Yöntem: Ocak 2010-Ocak 2012 tarihleri arasında Bakırköy Dr Sadi Konuk Eğitim ve Araştırma Hastanesi Kadın Hastalıkları ve Doğum Kliniğinde operatif histeroskopi yapılmıs 120 olgunun retrospektif kohort çalışması yapıldı. Bulgular: Araştırmaya 120 hasta dahil edildi. Hastaların ortalama yaşı 44.33'dü. Operatif histeroskopi için en sık karşılaştığımız endikasyon endometrial polipti. İşlemle ilişkili olarak 4 olguda komplikasyon gelişti. Sonuç: Histeroskopi güvenli ve efektif, komplikasyon oranları düşük minimal invaziv bir prosedürdür.
Operatif Histeroskopi: Bir Eğitim Hastanesinin Deneyimi